1975
DOI: 10.1136/hrt.37.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and evaluation of mitral valve disease using transseptal Doppler ultrasound catheterization.

Abstract: In 33 patients with confirmed mitral valve disease, the mitral valve flow velocity traces were recorded by means of a directional Doppler ultrasonic velocimeter using the transseptal route, and correlated with the clinical and haemodynamic data. In all cases, characteristic anomalies of the mitral flow velocity patterns were noted and could be related to the type of lesion, stenosis, regurgitation, or a combination of these. Furthermore, specific patterns of the flow velocity traces were shown to correlate sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…It is, therefore, difficult to conceive how augmentation of 'M' could be accounted for by postulating an increase in the velocity of flow through a diminishing orifice when there has been insignificant travel of the ball from the apex to the base of the prosthesis. Using a transseptal Doppler ultrasound technique, Kalmanson et al (1975) have shown that the velocity of blood flow across the mitral valve is decreasing at this time.…”
Section: Resultsmentioning
confidence: 99%
“…It is, therefore, difficult to conceive how augmentation of 'M' could be accounted for by postulating an increase in the velocity of flow through a diminishing orifice when there has been insignificant travel of the ball from the apex to the base of the prosthesis. Using a transseptal Doppler ultrasound technique, Kalmanson et al (1975) have shown that the velocity of blood flow across the mitral valve is decreasing at this time.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2A) mais pour la valvule mitrale, la voie transseptale adoptée nous a obligés à modifier la tête en bout de cathéter pour traverser la paroi septale en la rendant orientable pour s'adapter à sa configuration (VUS 185, Figure 2B). Les courbes chez l'homme normal et pathologique ont succédé aux tracés expérimentaux [11][12][13][14][15]. (Figure 1 A).…”
Section: Cb : Votre Dernier Article Paru En Mai 2015 [2] Figure Danunclassified
“…À droite, schéma de la courbe de vélocité instantanée du flux mitral : aux mêmes critères morphologiques qu'à droite s'associent des critères chronologiques rigoureux et spécifiques représentés pour chaque composante des courbes par rapport aux différentes phases du cycle cardiaque y compris les plus minimes, tels la contraction isovolumique, la relaxation ou les mouvements valvulaires. ci: contraction isométrique ; mo : ouverture mitrale ; S : onde systolique ; D : onde protodiastolique de remplissage rapide (la dénomination E pour échographie, a été adoptée ultérieurement) ; A : onde présystolique liée à la contraction auriculaire ; ECG : électrocardiogramme ; PCG : phonocardiogramme ; S1, S2, S3, S4 : bruits du coeur ; LA, LV : oreillette et ventricule gauches ; MFV : mitral flow velocity (reproduit d'après [11] et [15] Figure 3B). Il n'y avait plus qu'à travailler !…”
Section: Cb : Votre Dernier Article Paru En Mai 2015 [2] Figure Danunclassified
“…(2) This is not true in diseased valves, whose velocity profiles are irregular and asymmetrical (Kalmanson et al, 1975b;Whamond and Taylor, 1976). This stresses the necessity for carefully exploring the various sites of the mitral annulus, lest one type of lesion is overlooked.…”
Section: Effect Of Velocity Profilesmentioning
confidence: 99%